PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA TRIGO FUN BERBASIS GAME EDUKASI MENGGUNAKAN ADOBE ANIMATE PADA MATERI TRIGONOMETRI - Fibby Syaeful Abdullah; Tri Nova Hasti Yunianta (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to develop a mathematics education game on Trigonometry material. The type of this research is research and development (R & D) using the ADDIE development model. The steps consist of: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Media validation is carried out by material experts and media experts. Material validity reached 78% in the good category and media validity reached 96.43% in the very good category. Media trials were conducted at SMK Negeri 2 Salatiga class XI TEI A on 35 students and produced a practical index of 98% in the very good category. The results of media implementation showed that after using the media, experiencing an increase in learning outcomes of 1.1814 was included in the high increase category. Based on the results of the study it can be concluded that the media mathematics education game is valid, practical, and effective to use.